RELATIONSHIP BETWEEN SOCIAL VULNERABILITY AND THE FOOD AND NUTRITION INSECURITY IN ADULTS AND THE ELDERLY (Interdisciplinary Studies Journal, 2025)
Social vulnerability is a factor that can contribute to food and nutritional insecurity (FNI), which is regarded as a global challenge. Given the complexity of this issue, an integrative literature review was conducted, highlighting health applicability across four categories: FNI assessment methods, obtained FNI levels, and associations with risk factors. Studies indicate that, in Brazil, FNI is strongly associated with factors such as low income, unemployment, and low educational attainment, especially among household heads, and is further exacerbated by high household density, including minors under 18, and limited participation in social programs. The COVID-19 pandemic intensified these challenges, underscoring the urgent need for policies directed at vulnerable populations. Groups such as Black women, low-income elderly individuals, and residents of the North and Northeast regions face additional barriers to accessing food. Among the elderly, food insecurity is linked to depressive symptoms, while households with mothers suffering from mental disorders face a higher risk of severe FNI. The lack of assistance programs and the prevalence of informal employment worsen the problem, highlighting the need for approaches that incorporate food security and psychological support to mitigate inequalities and promote the fundamental right to food.
Keywords: Social Vulnerability; Food and Nutritional Insecurity; Adults and Elderly